Antioxidant and Antimicrobial Activities of Nerium Oleander Plant - Hasoon, Buthaina Abdul-Hamza (Al-Nahrain Journal of Science, 2018)
The green synthesis of Ag nanoparticles was prepared biologically in the presence of Nerium oleander extract and examined by UV-Vis spectrophotometer, Infrared (IR) spectroscopy and scanning electron microscopic (SEM) to characterize Ag nanoparticles. The effect of alcoholic extract alone, Ag nanoparticles determined on some pathogenic microorganisms. The alcoholic extract showed no considerable influence on the growth of tested strains, while the synthesised Ag nanoparticles show different effect on the growth of the microbial species. .The highest inhibition zone was shown on E.coli reaching (31mm) followed by P. aeroginosa (30 mm), S. aurous with inhibition zone reached to (23mm), K. pneumonia (22mm), and C.albicans (20mm). The effect of antibiotic (Gentamycin) has been studied alone on microbial growth with inhibition zone (17 mm) on C. albicans followed by E.coli with (13mm), and finally in S.aurous inhibition zone reached (15mm). The antimicrobial effect of (alcoholic extract- Gentamycin) was tested after mixing togathor which showed variotion with the highest effect on C. albicans in (19 mm), followed by S. aurous, and E.coli in (13 mm, 15 mm). respectively, K. pneumonia,, P. aeroginosa showed no inhibiting effect by alcoholic extract- Gentamycin complex. The ability of crude alcoholic extract to remove free radicals was determined by estimating antioxidant activity. The activity of the plant extract on the DNA molecules in vitro showed low absorbance values related to the increase in the concentration of ethanolic extract.